2010
DOI: 10.1007/s11239-010-0492-2
|View full text |Cite
|
Sign up to set email alerts
|

The AVAIL ME study: a multinational survey of VTE risk and prophylaxis

Abstract: Venous thromboembolism (VTE) is a major public health issue that is frequently underestimated. The primary objective of this multinational survey was to identify patients at risk for VTE, and to define the rate of patients receiving appropriate prophylaxis in the Middle Eastern region. Standardized case report forms were filled by trained individuals on one predefined day in selected hospitals. Data were then entered and analyzed by independent biostatisticians. Risk was categorized according to American Colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
32
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 47 publications
7
32
1
2
Order By: Relevance
“…There is some skepticism about the benefits of VTE prophylaxis especially in the elderly [2]. During the last decade, studies using either large datasets [3][4][5] or single center experiences [6,7] reported that between 30 and 74% of the acutely ill medical patients received VTE prophylaxis. In the multinational, crosssectional ENDORSE study [8] 60.5% of medical patients at risk did not receive prophylaxis according to the ACCP-2004 guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…There is some skepticism about the benefits of VTE prophylaxis especially in the elderly [2]. During the last decade, studies using either large datasets [3][4][5] or single center experiences [6,7] reported that between 30 and 74% of the acutely ill medical patients received VTE prophylaxis. In the multinational, crosssectional ENDORSE study [8] 60.5% of medical patients at risk did not receive prophylaxis according to the ACCP-2004 guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…15 The appropriate prophylaxis according to Caprini score was 59.9%, which is double the percentage reported by the study conducted in the same institution several years ago, which was 26%. 13 These values show an improvement in the frequency of appropriate VTE prophylaxis.…”
Section: Assessment For Vte Management In Hospitals In the Middlementioning
confidence: 54%
“…It was conducted to properly evaluate the status of anticoagulation practices in the Middle East and to serve as a foundation for attempts at quality improvement 15. The study included countries from the Middle East (Kingdom of Saudi Arabia, Lebanon, Syria, and United Arab Emirates), and from Central Asia (Georgia, Iran, and Kazakhstan) 15.…”
Section: Results From the Avail Me Studymentioning
confidence: 99%